Defective DNA damage repair leads to frequent catastrophic genomic events in murine and human tumors - Ratnaparkhe, Manasi; Kool, Marcel; Jauch, Anna; Kumar, Rajiv; Pfister, Stefan; Zapatka, Marc; Lichter, Peter; Ernst, Aurélie (Nature Communications, 2018)
Chromothripsis and chromoanasynthesis lead to locally clustered rearrangements affecting one or a few chromosomes, but their impact on cancer development and progression is unclear. Here the authors analyse the role of DNA repair factors in brain tumors by whole-genome sequencing of tumors from mouse models of medulloblastoma or high grade gliomas.
Gesehen am 08.05.2019